THE INFLUENCE OF THE SURVEY, QUESTION, READ, RECITE REVIEW, AND REFLECT (SQ4R) METHOD TOWARD THE STUDENTS’ READING COMPREHENSION (A STUDY OF META-ANALYSIS) (International Conference on Social and Islamic Studies, 2021)
This research aims to analyze the average level of influence of the SQ4R method onreading comprehension as a whole, based on education levels, and based on the regions. The research method used is a quantitative method with a meta-analysis design, namely by analyzing the results of research that have been published nationally related to the influence of the SQ4R method on reading comprehension. The document sources analyzed in this research were twenty articles and thesis obtained through Google Scholar search published in the 2015-2021 range covering the educational levels of Elementary School, Junior High School, Senior High School, and University. The instrument used coding sheet that summarizes the data and information of the articles and thesis. Based on the average level of influence of the SQ4R method on reading comprehension as a whole is 0.893 high category. The average level of influence of the SQ4R method on reading comprehension based on education levels, in Elementary School is 0.741 medium category, Junior High School is 0.961 high category, Senior High School is 0.988 high category, and University is 0.594 medium category and also the average level of influence of the SQ4R method on reading comprehension based on regions, Java Region 0.843 high category, Bali 0.922 high category, Lampung 0.339 small category, Kalimantan 0.406 small category, Sumatera 0.943 high category, Aceh 0.989 high category and Riau 0.571 medium category. The conclusion that the average level of influence SQ4R method reading comprehension as whole is 0.839 in high category. Based on educational levels, the SQ4R method on reading comprehension is suitable to conduct for all levels of education, and Based on regions, in high and medium category is Java, Bali, Sumatera, Aceh and Riau, it means that the SQ4R method on reading comprehension many gave contributions in five of regions.